Widespread Biases in Ecological and Evolutionary Studies. (10th July 2019) - Culumber, Zachary W; Anaya-Rojas, Jaime M; Booker, William W; Hooks, Alexandra P; Lange, Elizabeth C; Pluer, Benjamin; Ramírez-Bullón, Natali; Travis, Joseph
Abstract: There has been widespread discussion of biases in the sciences. The extent of most forms of bias has scarcely been confronted with rigorous data. In the present article, we evaluated the potential for geographic, taxonomic, and citation biases in publications between temperate and tropical systems for nine broad topics in ecology and evolutionary biology. Across 1, 800 papers sampled from 60, 000 peer-reviewed, empirical studies, we found consistent patterns of bias in the form of increased numbers of studies in temperate systems. Tropical studies were nearly absent from some topics. Furthermore, there were strong taxonomic biases across topics and geographic regions, as well as evidence for citation biases in many topics. Our results indicate a strong geographic imbalance in publishing patterns and among different taxonomic groups across a wide range of topics. The task ahead is to address what these biases mean and how they influence the state of our knowledge in ecology and evolution.